Прізвища Рівненщини із суфіксом -ськ- у контексті германо-слов’янського мовного розвитку - Шийка, Світлана (Slavia Orientalis, 2026)
The article is devoted to the study of surnames of the Rivne region with the suffix -s'k- within the context of Germanic-Slavic linguistic development. It is noted that the suffix of relative adjectives -s'k- has ancient Indo-European origins, most probably migrated to the Proto-Slavic language from Germanic languages. Proper personal names with this suffix and its variants are known from the Rus' chronicles, and during the course of social evolution they actively spread within the territory of the Rivne region and the locally adjacent Slavic lands of Ukraine, Poland and Belarus. Most regional surnames are specific from the point of view of motivational semantics and the word-forming system of the Ukrainian language, formed in a lexical-semantic way from words of appellative vocabulary, primarily from toponymic adjectives, some of them are morphological derivatives from various forms of personal names, nicknames (from anthroponymic and from appellative), surnames modelled on toponymic proper personal names.